Industrialization of sandwich composite panels for portable outdoor tabletops - Wen Yu; Robert Langer (PLoS ONE, 2026)
Sandwich composite panels offer a promising pathway for developing lightweight yet mechanically robust portable outdoor tabletops, but their industrialization outside traditional aerospace and transportation sectors remains challenging. This study investigates how sandwich composites can be adapted for mass‑market outdoor tabletops by linking market‑driven requirements to engineering design decisions. Five representative panel configurations were developed, varying in core materials, face‑sheet systems, surface finishing, edge‑sealing strategies, and fastening solutions. A structured evaluation matrix was established to assess both material‑level and product‑level performance, aligned with customer‑relevant requirements, applicable standards, and company‑defined acceptance criteria. Results show that industrial feasibility is governed not by any single metric but by the coupled interactions among material selection, surface durability, moisture‑resistant edge sealing, fastening reliability, and manufacturability-cost trade‑offs. Blind rivets emerged as a practical fastening solution, while surface durability and thermal stability were strongly influenced by the combined behavior of finishing chemistry and substrate. The findings establish practical architecture-performance relationships and outline viable industrialization pathways for mass‑market portable outdoor tabletops based on sandwich composite panels.